Feast day of St. John Baptist de La Salle - Salazar, Rodrigo (Animo Repository, 1983)
This feast day of St. John Baptist de La Salle was celebrated and also coincided with the Silver Jubilee of the De La Salle Catechetical Center. On the occasion, the St. John Baptist de La Salle Medal was conferred on Dr. Rodrigo Salazar and his wife Mrs. Salvacion Crisol-Salazar.